2020
DOI: 10.3390/pharmaceutics12060546
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cocrystallization-Mediated Altered Crystallographic Properties on the Tabletability of Rivaroxaban and Malonic Acid

Abstract: The present work aims to understand the crystallographic basis of the mechanical behavior of rivaroxaban-malonic acid cocrystal (RIV-MAL Co) in comparison to its parent constituents, i.e., rivaroxaban (RIV) and malonic acid (MAL). The mechanical behavior was evaluated at the bulk level by performing “out of die” bulk compaction and at the particle level by nanoindentation. The tabletability order for the three solids was MAL < RIV < RIV-MAL Co. MAL demonstrated “lower” tabletability because of its lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…It is important to improve the oral bioavailability of RIV to reduce dosing frequency and thus to improve patient compliance. Recently, several techniques have been utilized to improve the solubility and bioavailability of RIV such as cocrystals ( Kale et al, 2020 ), amorphous solid dispersions ( Metre et al, 2018 ), microemulsions ( Wingert et al, 2018 ), self-nanoemulsifying drug delivery system ( Xue et al, 2018 ), and micelles ( Cao et al, 2016 ). Among these strategies, cocrystals have attracted great interest and are a promising strategy to modify the physical-chemical properties of solid-state materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to improve the oral bioavailability of RIV to reduce dosing frequency and thus to improve patient compliance. Recently, several techniques have been utilized to improve the solubility and bioavailability of RIV such as cocrystals ( Kale et al, 2020 ), amorphous solid dispersions ( Metre et al, 2018 ), microemulsions ( Wingert et al, 2018 ), self-nanoemulsifying drug delivery system ( Xue et al, 2018 ), and micelles ( Cao et al, 2016 ). Among these strategies, cocrystals have attracted great interest and are a promising strategy to modify the physical-chemical properties of solid-state materials.…”
Section: Introductionmentioning
confidence: 99%
“…RIV is a Biopharmaceuticals Classification System (BCS) Class II drug with low oral bioavailability ( Kushwah et al, 2021 ). Rivaroxaban-malonic acid cocrystal (RIV-MAL) could improve the tabletability and increase the water sorption of RIV ( Kale et al, 2020 ; Kale et al, 2019 ). However, to the best of our knowledge, the study and application of improved permeability and bioavailability of RIV by cocrystals has not yet been reported ( Grunenberg et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are various practical approaches to improve the solubility of these include the use of particle size manipulation via micronization and nanonization, use of complexing agents such as cyclodextrins. The preparation of high energy drug states related to polymorphic or amorphic transformations use of co-solvents, micellar solutions and lipid based systems for lipophilic drugs are also one of the techniques to improve the solubility behaviour [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers investigated a relationship between crystal structure and mechanical properties [13][14][15][16][17][18][19][20]. Kale et al reported a better tableting performance of rivaroxaban-malonic acid (2:1) cocrystal than that of rivanoxaban due to the presence of flat slip plane that enhances the plasticity of rivaroxaban-malonic acid cocrystal [21]. To continue to improve the solubility of the current cocrystal, herein we reported the performance of the mechanical properties of mefenamic acid (MFA) : nicotinamide (NIC) cocrystal.…”
Section: Introductionmentioning
confidence: 99%